Structure of the Rna15 RRM–RNA complex reveals the molecular basis of GU specificity in transcriptional 3′-end processing factors - Pancevac, Christina (Oxford University Press, 2010)
Rna15 is a core subunit of cleavage factor IA (CFIA), an essential transcriptional 3′-end processing factor from Saccharomyces cerevisiae. CFIA is required for polyA site selection/cleavage targeting RNA sequences that surround polyadenylation sites in the 3′-UTR of RNA polymerase-II transcripts. RNA recognition by CFIA is mediated by an RNA recognition motif (RRM) contained in the Rna15 subunit of the complex. We show here that Rna15 has a strong and unexpected preference for GU containing RNAs and reveal the molecular basis for a base selectivity mechanism that accommodates G or U but discriminates against C and A bases. This mode of base selectivity is rather different to that observed in other RRM-RNA structures and is structurally conserved in CstF64, the mammalian counterpart of Rna15. Our observations provide evidence for a highly conserved mechanism of base recognition amongst the 3′-end processing complexes that interact with the U-rich or U/G-rich elements at 3′-end cleavage/polyadenylation sites.